Experiences of nurses involved in air ambulance service: A qualitative study - Wang, Kuei-Ying; Hu, Fang-Wen; Yu, Shu-Chen; Lin, Yohana Yobelina; Han, Chien-Ying (Jurnal Ners, 2024)
Introduction: Nurses undertaking air ambulance service encounter environmental, equipment, and personnel limitations during their work. Moreover, they must cope with various types of injuries and illnesses, as well as changes in patient conditions. These factors pose a significant pressure on nurses. Currently, there is a lack of qualitative research on the experiences of nurses performing air ambulance tasks. The purpose of this study is to explore the experiences of nurses undertaking air ambulance service, with a focus on capturing their personal perceptions regarding this field of work. Methods: Twelve nurses were selected using purposive sampling, and semi-structured interviews were conducted to collect data. Content analysis was used to analyze the data. Results: The analysis identified three major themes: "Ambiguous and risky emergency missions," "Challenges during air transfer," and "Nurses' personal limitations.” Eight categories were formulated within these themes, including "Mission uncertainty," "Urgency of medical conditions," "Hazards at high altitude," "Cabin environment limitations," "Inadequate equipment," "Incomprehensive operating mechanisms," "Physical discomfort," and "Recognition of professional shortcomings." Conclusions: Improving the performance and well-being of nurses engaged in air ambulance services necessitates the implementation of a psychological adaptation program. This includes the utilization of psychological stress assessment tools or engaging in role-playing activities. Successful patient rescues demand the establishment of comprehensive standard operating procedures, involving an interprofessional team. Supporting nurses in adeptly managing challenges during air ambulance services requires an expanded scope of education and training, facilitated through initiatives like situational simulation and similar approaches.